Environmental risk assessment of carbosulfan on target and non-target beetles when used as white grub larvicide in the cork oak forest of Mamora (Morocco) - Fegrouche, R; Kadiri, N; Ghailoule, D; Kadiri, Z Atay; Lumaret, J -P. (INTERNATIONAL JOURNAL OF PEST MANAGEMENT, 2014)
The protection of new cork oak plantations against the larvae of the beetle Sphodroxia maroccana (Melolonthidae), which destroy the roots of newly planted trees, was provided for many years in the forest of Mamora in Morocco by the use of carbosulfan, usually formulated as dry granules for direct incorporation into the soil at planting. Ecotoxicological tests were conducted in the laboratory on S. maroccana and on two non-target beetle species, namely Pachychila obtusecostata and Pimelia platynota (Tenebrionidae), to measure the acute effects of carbosulfan and evaluate the potential risk associated with inappropriate practices. The mortality was measured at both 4 d and 7 d after ingestion of a known quantity of carbosulfan. The recommended dose by the manufacturer was exceeded by at least four-fold in the Mamora Forest, with obvious environmental risks. Risks were identified for wildlife when the pesticide is misused and spread on the soil around the plants.
Keywords: carbosulfan; Cork oak; environmental risk; Melolonthidae; Morocco; mortality; Pachychila obtusecostata; Pimelia platynota; Sphodroxia maroccana; Tenebrionidae